Does Consultation Time Influence Patient Perception of Provider Communication Style, Patient Satisfaction, and Word of Mouth Recommendation in India? A mediation analysis - Payal Mehra (ACHSM, 2018)
Background: In medically underserved developing countries such as India, the length of the consultation is often compromised; providers, it appears, have lost their natural empathetic tendencies and try to substitute talk with techniques and procedures. Despite this, surprisingly, patient satisfaction is high in India. This raises questions on the importance of understanding how patients feel about the clinical consultation length and the way it affects their satisfaction. In this context, this study analysed if the time spent with the patient predicted different changes to patient satisfaction with the provider and word of mouth recommendation. Methods: This cross sectional study comprised a sample of working Indian adults (N=501), completing communication competence measures and indicating their satisfaction and word of mouth recommendation potential. The four step Baron and Kenny's model of mediation analysis, apart from the GLM and factor analysis, was used for the analysis Results: Findings showed that the communication style of the providers positively influenced the health outcomes such as patient satisfaction and word of mouth recommendation, and the length of direct consultation time mediated this relationship.  Gender wise, male patients were more likely to complain about poor communication competency of the providers and less consultation time than female patients  Conclusion: We conclude that patients positively associate a longer clinical consultation time with empathetic and competent providers and be willing to recommend him/her to others. However due to extreme paucity of qualified providers in India, patients generally ignore or suffer problems related to time or communication style.